Surgical resection for duodenal neuroendocrine neoplasia: outcome, prognostic factors and risk of metastases - Nießen, Anna; Bergmann, Frank; Hinz, Ulf; Schimmack, Simon; Hackert, Thilo; Büchler, Markus W.; Strobel, Oliver (European journal of surgical oncology, 2020)
Background - Clinical management of duodenal neuroendocrine neoplasms (dNEN) is controversial. The aim of this study was to assess the outcome of surgical management and to identify risk factors for metastatic disease. - Methods - Patients undergoing surgery for dNEN were retrospectively analysed. Clinicopathologic features, perioperative outcome and survival were assessed. A literature review with focus on risk factors for metastatic disease was additionally performed. - Results - 24 patients were identified. Out of 22 patients presenting with their primary tumour, 20 patients underwent curative resection and 18 patients received curative resection with systematic lymphadenectomy. 17 patients underwent formal oncological resection. Surgical mortality was 1 out of 24 patients. The 5-year overall survival rate was 67% in the entire cohort, 71% in patients undergoing resection for their primary tumour, 72% for patients undergoing curative resection with systematic lymphadenectomy, 75% for pN0 and 70% for pN1 tumours. Lymph node metastases were identified in 15 patients undergoing systematic lymphadenectomy, including 9 of 14 patients with tumours smaller than 2 cm, and 6 of 10 patients with G1 tumours. Literature review confirmed a high risk of metastases in small (58%) or G1 (24%) tumours. Tumour grade and angioinvasion were significantly associated with overall and disease-free survival. - Conclusion - Even well differentiated or small dNEN harbour a considerable risk of metastases. These data challenge the concepts of surveillance, local resection and endoscopic management for dNEN based on size and grading. Angioinvasion was identified as a strong negative predictor of overall and disease-free survival in dNEN.
Gesehen am 18.03.2021